PENGEMBANGAN MEDIA PEMBELAJARAN PAPAN FLANEL KATA PADA MATERI MENULIS KALIMAT KELAS II SD NEGERI JATIASIH IX KOTA BEKASI - Handayani, Irda Tri; Lutfi, Lutfi (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
Writing is a language skill that is taught along with the other three language skills. The aims of this study were to (1) produce the development of word flannel board learning media for Indonesian language learning materials for writing sentences, (2) test the results of the feasibility of word flannel board learning media, (3) find out students' responses related to word flannel board learning media. The type of research used in this research is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data analysis techniques used are interviews, questionnaires, and documentation. The results of this development trial went through two stages of small group trials and large group trials. The results of the small group trial reached 81.5%, with very valid criteria, and the results of the large group trial reached 82.5% with very valid criteria. The developed learning media is validated by material experts, linguists, and media experts. The validation results of media experts obtained 84.43% with very valid criteria, the validation results of material experts obtained 87.77% with very valid criteria, and the validation test of linguists obtained 96.66% with very valid criteria. Based on these results, this learning media is feasible to use. By using the word flannel board learning media can provide motivation for students in writing sentences in the learning process